2015
DOI: 10.1123/jpah.2014-0271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Social and Physical Environment on Children’s Independent Mobility to Neighborhood Destinations

Abstract: Background:Relationships between context-specific measures of the physical and social environment and children’s independent mobility to neighborhood destination types were examined.Methods:Parents in RESIDE’s fourth survey reported whether their child (8–15 years; n = 181) was allowed to travel without an adult to school, friend’s house, park and local shop. Objective physical environment measures were matched to each of these destinations. Social environment measures included neighborhood perceptions and ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 50 publications
4
44
0
2
Order By: Relevance
“…Overall, 56% of children had an older sibling (8–17 years), 26% had an older sibling of the same gender, 53% had a dog at home and 34% of parents perceived that it was unsafe for children to independently move around the neighbourhood. Detailed sample characteristics have been reported previously 17 . Being male and older (vs. female and younger) was associated with increased odds of being independently mobile (results not shown).…”
Section: Resultsmentioning
confidence: 60%
“…Overall, 56% of children had an older sibling (8–17 years), 26% had an older sibling of the same gender, 53% had a dog at home and 34% of parents perceived that it was unsafe for children to independently move around the neighbourhood. Detailed sample characteristics have been reported previously 17 . Being male and older (vs. female and younger) was associated with increased odds of being independently mobile (results not shown).…”
Section: Resultsmentioning
confidence: 60%
“…As urban density and the number of dwellings with no or small yards increases, providing local spaces and facilitating safe play within the local neighborhood is increasingly important 88 . Designing neighborhoods that encourage children's health and wellbeing includes access to local destinations, including green space and nature, and local infrastructure and services 70,89 . We know that destinations such as schools, recreation venues, and child and health care services all have inherent functional roles, but they can also serve as physical places for social interaction and developing networks of support 35 .…”
Section: Access To Local Destinations and Naturementioning
confidence: 99%
“…This idea is supported through research on the psychology of decision making that has shown risk preferences to be influenced by a range of situational factors 20. More specifically related to parenting, Christian et al 19 reported that independent mobility of children aged 8–15 years allowed by parents was related to factors in the physical environment as well to social norms.…”
Section: Discussionmentioning
confidence: 97%